2019
DOI: 10.5194/wes-4-233-2019
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative yaw stability analysis of free-yawing downwind turbines

Abstract: Abstract. This article qualitatively shows the yaw stability of a free-yawing downwind turbine and the ability of the turbine to align passively with the wind direction using a model with 2 degrees of freedom. An existing model of a Suzlon S111 upwind 2.1 MW turbine is converted into a downwind configuration with a 5∘ tilt and a 3.5∘ downwind cone angle. The analysis shows that the static tilt angle causes a wind-speed-dependent yaw misalignment of up to −19∘ due to the projection of the torque onto the yaw be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Such yaw systems could be cost-efficient as they simplify the turbine control, and reduce operation and maintenance costs, as they could purely be used for cable unwinding. However, Wanke et al (2019c) showed on an example of a 2.1MW turbine with a tilted rotor that such systems align passively at high yaw angles for high wind speeds resulting into significant power loss. The study concluded that tilt angle, cone angle and blade stiffness would need to be specifically designed for a free yawing downwind configuration.…”
mentioning
confidence: 99%
“…Such yaw systems could be cost-efficient as they simplify the turbine control, and reduce operation and maintenance costs, as they could purely be used for cable unwinding. However, Wanke et al (2019c) showed on an example of a 2.1MW turbine with a tilted rotor that such systems align passively at high yaw angles for high wind speeds resulting into significant power loss. The study concluded that tilt angle, cone angle and blade stiffness would need to be specifically designed for a free yawing downwind configuration.…”
mentioning
confidence: 99%
“…At 16 m s −1 the drift of the platform stabilises around 39 º. At this yaw position, the destabilising yaw moments generated by the rotor are compensated by restoring yaw moments that appear with the yaw rotation, such as the one due to the weathervanning effect and the restoring moment that is generated at the rotor under yawed inflow wind, as reported by Wanke et al (2019).…”
Section: Blade-level Analysis Of the Causes Of Yaw Momentmentioning
confidence: 64%
“…This type of turbines offer the advantage of having a passive yaw alignment capacity that does not require heavy yaw mechanisms. Wanke et al (2019) explain that, when there is some 2 https://doi.org/10.5194/wes-2022-86 Preprint. Discussion started: 11 October 2022 c Author(s) 2022.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the natural weather vane properties of downwind rotors, another potential benefit that is not captured in traditional LCOE studies is the opportunity to downsize the yaw actuator or motors 31 . Several works in literature have investigated the topic of free‐yaw downwind rotors, both numerically 32,33 and experimentally with scaled wind tunnel models 34,35 . The experimental studies generally returned promising results, whereas the numerical studies found conditions where the free‐yaw rotor generated large yaw misalignments and power losses.…”
Section: Passive Rotor Yawingmentioning
confidence: 99%